The hollow dead - Coates, Darcy (Coates, Darcy. Gravekeeper, 2024)
"When Keira first woke alone in a strange forest, she remembered only two things: that she could speak with the dead, helping them move on from the mortal world, and that sinister mask-wearing men were hunting her. She had no idea what she'd done to earn their hatred or what dangerous secrets she may have uncovered. Until now. Peeling back layer upon layer of the mystery surrounding her origins, Keira has finally learned that the strange masked men work for Artec, an organization profiting off spectral energy produced by hundreds of chained, tormented souls. Their goal is to spread their macabre cemeteries across the world, using the agony of the dead to extend their power and reach--and only Keira and her loyal group of friends have a hope of stopping them. But there are still mysteries to uncover in Keira's foggy memories, and as she prepares to fight for the souls of the tormented dead, what she doesn't know about her own past may ultimately come back to haunt her"--